Archivi aperti e comunicazione scientifica Open Archives and Scientific Communication - Antonella De Robbio (Saperi storici e nuove tecnologie, 2007)
In the last years, institutional repositories of preprints and scholarly publications have become a peak experience in the digital library environment, enabling the involvement of authors and scientific communities in a free and shared access to the results of research, and to its circulation trough the web. This volume collects a series of essays, both published and unpublished, that Antonella De Robbio wrote with respect to the issue of scientific information, and to the reply given by the Open Access Movement (OAI). The collection aims to a double purpose: first, to fill the gap in the lacking Italian bibliography concerning Open Archives; second, to take stock of the difficult situation of the Open Access Movement, and of the hope of its advocates that this movement could promote a democratic and immediate circulation of scientific knowledge.